The Use of Adjacency Pairs in Big Hero 6 Film - Fitri, Annisa; Valiantien, Nita Maya; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research analyzed the conversation of the characters using adjacency pairs and insertion sequences. The purposes of the research are to identify the types of adjacency pairs and to find out the types of insertion sequences in the Big Hero 6 film. The approach used in this research is conversation analysis, specifically using the adjacency pairs theory of Paltridge and the insertion sequence theory of Levinson. This research is classified into descriptive qualitative research, while the data are words and sentences in the conversation. Based on the result of the analysis, the researchers found seven types of adjacency pairs in the film. The seven types are complaint-apology, greeting-greeting, offer-acceptance, assessment-agreement, blame-denial, request-agreement, and question-answer sequence. This research also found two types of insertion sequences which are request-question-answer-acceptance and repair sequence. The result of the research showed that Baymax can adapt to the human environment with their limited language by hearing explanations given by the other characters in the film. This research revealed that the use of adjacency pairs can make the conversation clearer and insertion sequence can help to understand the meaning of the expression in words by the explanation.